The disconnect between textbook and research: Inductive versus deductive approaches to grammar in first-year German college textbooks - Pittman, Iulia (Glottodidactica, 2021)
Foreign language teaching methodologies have changed noticeably in the last hundred years. The emphasis on grammar has decreased, while the focus on communication has increased. Rather than quantitative in nature, these changes concern themselves more with the qualitative question of how grammar is taught. Two common approaches to grammar teaching are the inductive and deductive approach. While they both fall under the explicit grammar-teaching umbrella, research strongly points toward an advantage of the inductive grammar teaching approach. Therefore, a principal question that this article seeks to answer is which approach is more commonly found in current first-year German college textbooks. A detailed analysis of how eleven relevant textbooks present their grammar lessons reveals that the overwhelming majority (N=8) of the textbooks use the deductive approach. These findings indicate a significant disconnect between grammar presentation in textbooks and recent research on successful and effective foreign language teaching. It is strongly recommended that textbook authors and colleagues involved in the textbook selection process be more informed with the research findings in SLA and be instrumental in seeing that these changes are reflected in textbooks and language teaching curricula.